Vaccine-induced neutralizing antibody responses to seasonal influenza virus H1N1 strains are not enhanced during subsequent pandemic H1N1 infection - Mooij, Petra; Mortier, Daniella; Aartse, Aafke; Murad, Alexandre B.; Correia, Ricardo; Roldão, António; Alves, Paula M.; Fagrouch, Zahra; Eggink, Dirk; Stockhofe, Norbert; Engelhardt, Othmar G.; Verschoor, Ernst J.; et al. (Frontiers in Immunology, 2023)
The first exposure to influenza is presumed to shape the B-cell antibody repertoire, leading to preferential enhancement of the initially formed responses during subsequent exposure to viral variants. Here, we investigated whether this principle remains applicable when there are large genetic and antigenic differences between primary and secondary influenza virus antigens. Because humans usually have a complex history of influenza virus exposure, we conducted this investigation in influenza-naive cynomolgus macaques. Two groups of six macaques were immunized four times with influenza virus-like particles (VLPs) displaying either one (monovalent) or five (pentavalent) different hemagglutinin (HA) antigens derived from seasonal H1N1 (H1N1) strains. Four weeks after the final immunization, animals were challenged with pandemic H1N1 (H1N1pdm09). Although immunization resulted in robust virus-neutralizing responses to all VLP-based vaccine strains, there were no cross-neutralization responses to H1N1pdm09, and all animals became infected. No reductions in viral load in the nose or throat were detected in either vaccine group. After infection, strong virus-neutralizing responses to H1N1pdm09 were induced. However, there were no increases in virus-neutralizing titers against four of the five H1N1 vaccine strains; and only a mild increase was observed in virus-neutralizing titer against the influenza A/Texas/36/91 vaccine strain. After H1N1pdm09 infection, both vaccine groups showed higher virus-neutralizing titers against two H1N1 strains of intermediate antigenic distance between the H1N1 vaccine strains and H1N1pdm09, compared with the naive control group. Furthermore, both vaccine groups had higher HA-stem antibodies early after infection than the control group. In conclusion, immunization with VLPs displaying HA from antigenically distinct H1N1 variants increased breadth of the immune response during subsequent H1N1pdm09 challenge, although this phenomenon was limited to intermediate antigenic variants.